Influences of Operating Variables on Hydrodynamic Performance of Plunging Water Jet Downflow Bubble Column - I. Abdulaziz, Yasser; K. Salih, Issam; J. Mohammed, Thamer (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The hydrodynamics of a co-current down flow bubble column has been investigated with air – water system. A Perspex bubble column of 5cm in diameter and 1.5m height is used as a test contactor using nozzles of 7, 8 and 9 mm diameter for air-water distributing. The column is provided with three electro-resistivity needle probes for bubble detection. Experimental work is carried out with air flow rates from 0.09 to 0.45 m3/hr and liquid flow rates from 0.65 to 1.1m3/hr in order to study the effects of superficial gas velocity, nozzle diameter and liquid flow rate on the characteristics of hydrodynamic interactions viz. gas hold up, bubble diameter and bubble velocity by using two technical methods, direct height measurements for air-water mixture in the column and resistivity probe techniques. Gas hold up is found to be progressively increased with increasing superficial gas velocity and with decreasing liquid flow rate. Lower gas hold up is obtained with smaller nozzle diameter. However, gas hold up in two-phase zone is considerably higher than the corresponding value in mixing zone. The mean bubble velocity is increased with increasing superficial gas velocity, liquid flow rate and nozzle diameter for both mixing and two phase zones. Experimental data are found to be fairly fitted with the Drift Flux model of Zuber and Findly. The bubble diameter is considerably increased with increasing superficial gas velocity and with decreasing liquid flow rate, whereas it is slightly influenced by nozzle diameter. However, the bubbles in two-phase zone are relatively bigger than those observed in mixing zone. Finally, mathematical correlations have been developed from the experimental data to describe the gas hold up and bubble velocity in the uniform two-phase zone.